The effects of continuous contingent, random contingent and random negative stimulation on selected responses in a moment of stuttering - T, DATTATREYA (Journal of All India Institute of Speech and Hearing)
The present study attempted to investigate the effects of three schedules of negative stimulation on 8 stutterers. The three schedules were Continuous contingent, Random contingent and Random negative stimulation. The random schedules were predetermined. The responses stilnulatcd were repetitions in seven subjects and hesitation in one subject. Balanced Latin Square D sign was used to cancel out the order effects and to help in the calculation of residual effects of the three schedules on each other. Six subjects wefe used in the Balanced Latin Square Design. Residual effects were obtained by the analysis of variance for the group